Identification of miR-305, a microRNA that promotes aging, and its target mRNAs in Drosophila. - Ueda, M.; Sato, T.; Ohkawa, Y.; Inoue, Y.H. (Genes to cells : devoted to molecular & cellular mechanisms, 2018)
MicroRNAs (miRNAs) are involved in the regulation of important biological processes. Here, we describe a novel Drosophila miRNAs involved in aging. We selected eight Drosophila miRNAs, displaying high homology with seed sequences of aging-related miRNAs characterized in other species, and investigated whether the over-expression of these miRNAs affected aging in Drosophila adult flies. The lifespan of adults over-expressing miR-305, a miRNA showing high homology with miR-239 in C. elegans, was significantly shorter. Conversely, a reduction in miR-305 expression led to a longer lifespan than that in control flies. miR-305 over-expression accelerated the impairment of locomotor activity and promoted the age-dependent accumulation of poly-ubiquitinated protein aggregates in the muscle, as flies aged. Thus, we show that the ectopic expression of miR-305 has a deleterious effect on aging in Drosophila. To identify the targets of miR-305, we performed RNA-Seq. We discovered several mRNAs encoding antimicrobial peptides and insulin-like peptides, whose expression changed in adults upon miR-305 over-expression. We further confirmed, by qRT-PCR, that miR-305 over-expression significantly decreases the mRNA levels of four antimicrobial peptides. As these mRNAs contain multiple sequences matching the seed sequence of miR-305, we speculate that a reduction in target mRNA levels, caused by ectopic miRNA expression, promotes aging.